Effects of Optimized Fertilization and Organic Fertilizer Subsitution Technology on the Growth and Soil Fertility of Chinese Flowering Cabbage - Lan WEI; Zehuang WANG; Weisheng CHEN; Lianxi HUANG; Lihua TIAN; Zhongzhen LIU; Dongtian LAO; Qing HUANG (Guangdong nongye kexue)
【Objective】The optimized fertilization and organic fertilizer substitution technology is a national strategy to achieve environmental friendliness and maintain the quality of cultivated land, which is of great significance to achieving sustainable agricultural development. The study explores the effects of optimized fertilization and fertilizer reduction measures on the physical and chemical properties of vegetable soil, as well as the yield and quality of Chinese flowering cabbage in Jiangmen of Guangdong Province, with a view to providing theoretical basis and technical support for balanced and effective fertilization in vegetable fields.【Method】Jiangmen City of Guangdong Province, one of the vegetable supply bases for Hong Kong and the Pearl River Delta, was used as the research base. Field plot tests were conducted and seven treatments were set: the control (CK), customary fertilization (T1), optimized fertilization (T2), optimized fertilization + 15% organic fertilizer replacing N (T3), optimized fertilization + 30% organic fertilizer replacing N (T4), optimized fertilization + 15% biochar-based organic fertilizer replacing N (T5), and optimized fertilization + 30% biochar-based organic fertilizer replacing N (T6). The effects of seven treatments on the yield, leaf nutrient accumulation, and quality of Chinese flowering cabbage, as well as nutrients and physicochemical properties of soil were measured.【Result】Compared with conventional fertilization (except for the control), optimized fertilization and organic substitution treatments (T2-T6) had no significant effect on the yield of Chinese flowering cabbage. T2 had the highest yield (28.15 t/hm2), followed by T3 (26.35 t/hm2). The nutrient content was not affected by organic substitution. The accumulation of dry matter and nutrient elements had increased compared with T1, with T2 having the highest accumulation of dry matter (by an increase of 12.58%) and T6 having the highest accumulation of nitrogen, phosphorus, and potassium elements, which were 1.19, 1.18, and 1.18 times that of T1, respectively. However, the Vc and soluble sugar content of Chinese flowering cabbage increased (9.49%-22.63% and 18.96%-126.37%) under all treatments. The agronomic utilization efficiency of all treated fertilizers was higher than that of T1. T2 produced the highest agronomic utilization efficiency (N: 2.77, P: 7.38, K: 3.69), and agronomic utilization efficiency of T6 ranked the second (N: 2.17, P: 5.78, K: 2.89). The pH values of the treatments using organic substitution (T3-T6) were higher than those of single fertilizer application. Among them, T6 treatment had the largest difference from conventional fertilization (0.62 units), and the soil organic matter content of all treatments was higher than that of T1 (9.75%-34.31%).【Conclusion】Compared with customary fertilization, there is no reduction vegetable yield under all treatments. Optimized fertilization (T2) shows the highest agronomic efficiency. On the basis of comprehensive consideration of yield increase and quality improvement of Chinese flowering cabbage, benefit increase and soil property improvement, the optimized fertilization + 15% organic fertilizer replacing N combined is the best. Therefore, 15% organic fertilizer replacing N may be the most suitable fertilizer reduction and benefit increase mode for the cost of Chinese flowering cabbage in Jiangmen.